A Transforaminal Endoscopic Surgical Technique for Treating Lumbar Disc Herniation in the Setting of Spina Bifida. (9th March 2020) - Telfeian, Albert E.; Oyelese, Adetokunbo; Fridley, Jared; Ali, Rohaid; Cielo, Deus; Gokaslan, Ziya L.
Abstract : Recent literature suggests that adult patients with spina bifida receive surgery for degenerative disc disease at higher rates than the general population. However, sometimes the complex anatomic features of co-occurring spina bifida and lumbar disc herniation can significantly challenge standard surgical techniques. Here, the technical steps are presented for treating a foraminal lumbar 4-5-disc herniation in the setting of a patient with multifaceted degenerative and spina bifida occulta anatomy. Utilized is a minimally invasive approach that does not require general anesthesia or fusion and allows the patient to leave the same day. To the best of our knowledge, this is the first-reported case of endoscopic surgical decompression of a lumbar disc in a patient with spina bifida.